A case study: distribution of phosphorus pools in paddy soils in Melaka / Nur Asma Syafiqah Azizul - Azizul, Nur Asma Syafiqah (Faculty of Plantation and Agrotechnology, 2018)
Phosphorus (P) is one of the important nutrient in the soil which it will affected to the rice production if the availability of P is low. It is an essential nutrient for plants and animal although it is a non-renewable resource. The sampling location for the study is at Sg Rambai (SR) and Pengkalan Samak (PS). The soil characteristics that were collected in SR was found to contain sand 29%, silt 20% and clay 69% texture. The soil pH in SR is 5.02, aluminium (Al) 688.6 mg kg-1, iron (Fe) 287.9 mg kg-1 and soil organic matter (OM) 16.61 mg kg-1. Besides, soil characteristics in PS for the particle distribution of sand 22%, silt 54% and clay 24%. However, the soil pH in PS is 5.60, Al (98.9 mg kg-1), Fe (350.8 mg kg-1) and soil OM (7.71 mg kg-1). A sequential extraction procedure was used to identify the P fractions such as Bicarbonate-P, Hydroxide-P, Calcium-P, Occluded-P and total P and the relationship between P fractions and soil characteristics in rice fields in SR and PS, Melaka. Total amount of P between the two rice fields is in SR (552.2 mg kg-1) and PS (190.9 mg kg-1). The soils in SR had a higher amount of HCO3-P (60.51 mg kg-1) and OH-P (315.4 mg kg-1) levels than soils in PS.